1995
DOI: 10.1183/09031936.95.08071148
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil cationic protein and tidal flow volume loops in children 0-2 years of age

Abstract: E Eo os si in no op ph hi il l c ca at ti io on ni ic c p pr ro ot te ei in n a an nd d t ti id da al l f fl lo ow w v vo ol lu um me e l lo oo op ps s i in n c ch hi il ld dr re en n 0 0--2 2 y ye ea ar rs s o of f a ag ge e TFV loops were measured in 79 awake children (mean age 14 months). Minimum two wheezy episodes (mean 3.2) or minimum 4 weeks persistent wheeze were reported in 41 children (cases), whereas the 38 controls had no history of wheeze. Airways responsiveness (change in ratio of time until peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
15
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 27 publications
7
15
1
Order By: Relevance
“…This observation strengthens the likelihood that these lung function measurements reflect severity of OAD in young children, as has been previously reported [13,26]. Furthermore, it appears that the children who subsequently received ICS treatment had the greatest improvement in lung function by 2 yrs of age.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This observation strengthens the likelihood that these lung function measurements reflect severity of OAD in young children, as has been previously reported [13,26]. Furthermore, it appears that the children who subsequently received ICS treatment had the greatest improvement in lung function by 2 yrs of age.…”
Section: Discussionsupporting
confidence: 69%
“…Although there is debate on the standardisation and measurements in the youngest children, TFV measurements have been documented in the present study, in previous studies from the current authors [13,16,26] and others9 studies [12,30], to be sensitive enough to differentiate between children with and without OAD, as well as to detect adverse effects of maternal smoking in pregnancy [31,32]. It is, therefore, suggested that the present findings are representative of changes in lung function through early childhood, and can be used to document changes related to ICS treatment in groups of these young children.…”
Section: Advantages and Limitations Of The Present Studysupporting
confidence: 51%
“…12 The most commonly used parameters to describe the shape of the TFV loop have been tPTEF/tE and the corresponding VPTEF/VE. Although the time ratio is most commonly reported, [1][2][3][4][5][6][7][8][9]12,19 there is no agreement regarding the optimal ratio to discriminate between lung diseases and health. 2,3,18 The aim of the present study was to review our published data and determine whether the observed changes in ratios tPTEF/tE and VPTEF/VE 2,10 could be related to changes in respiratory rates and/or other physiological mechanisms in normal neonates 10 and in children with asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Tidal breathing parameters were determined by the TFV ratios, t PEF/t E and VPEF/VE, which have been shown to differ according to obstructive airways disease; t PEF/t E [10][11][12] and VPEF/ VE [10,11,13,14] have also predicted wheeze in children under 3 yrs of age (t PEF/t E) [5]. Respiratory mechanics were determined as: compliance of the respiratory system (Crs) as a measure of tissue and airways elasticity; and resistance of the respiratory system (Rrs) as a measures of airways size.…”
Section: Outcome Measuresmentioning
confidence: 99%